Opinions of the UNED Costa Rica student body on the academic changes generated in response to the COVID-19 emergency (Innovaciones Educativas, 2021)
Due to the health emergency caused by COVID-19 in 2020, changes occurred in the different social areas, these being very significant in the educational context. In the case of the Universidad Estatal a Distancia de Costa Rica [UNED] (State Distance University of Costa Rica), contingency measures were taken from the administrative and academic aspects to ensure the continuity of the educational processes of the different majors and programs. This article offers the most relevant findings of a study the main object of which was to know the opinion of the UNED students on those academic changes implemented during the first four months of 2020 as a result of the health emergency caused by COVID-19. A descriptive study was developed based on an online survey that included a sample of 443 students from this institution. In general terms, the population participating in the study does not present problems with regard to the possession of mobile devices and internet access. They used social networks as the main means to find out about the actions taken by the University. Similarly, the induction and support received from institutional officials to fulfill their academic tasks was valued positively. The contingency actions implemented to ensure the continuity of the student’s learning process during the emergency were positively perceived. The fact of having support from the beginning was highlighted, not only by the corresponding instance, but also with support and information from other agencies, which leads to the conclusion that the changes implemented as a result of the situation had results that tended to be positive for the participating student population.
Keywords: College student; distance education; Higher education; Digitization; Education and development